PCV3-associated disease in the United States swine herd. Issue 1 (1st January 2019) - Arruda, Bailey; Piñeyro, Pablo; Derscheid, Rachel; Hause, Ben; Byers, Emily; Dion, Kate; Long, Duane; Sievers, Chris; Tangen, Jon; Williams, Todd; Schwartz, Kent
ABSTRACT: Porcine circovirus-associated disease encompasses multiple disease syndromes including porcine circovirus 2 systemic diseases, reproductive failure, and porcine dermatitis and nephropathy syndrome. Until recently, porcine circovirus 2 was the only species associated with the porcine circovirus-associated disease. In this report, diagnostic investigations of thirty-six field cases submitted from multiple production systems, numerous sites and varied geographic locations demonstrated porcine circovirus 3 within lesions by in situ hybridization including fetuses with myocarditis, weak-born neonatal piglets with encephalitis and myocarditis, from cases of porcine dermatitis and nephropathy syndrome, and in weaned pigs with systemic periarteritis. Porcine circovirus 3 was detected by PCR in numerous fetuses and perinatal piglets at high viral loads (trillions of genome copies per mL of tissue homogenate). Samples from all cases in this study were assayed and found negative for porcine circovirus 2 by PCR. Metagenomic sequencing was performed on a subset of reproductive cases, consisting of sixteen fetuses/fetal sample pools. PCV3 was identified in all pools and the only virus identified in fourteen pools. Based on these data, porcine circovirus 3 is considered a putative cause of reproductive failure, encephalitis and myocarditis in perinatal piglets, porcine dermatitis and nephropathy syndrome, and periarteritis in swine in the United States.